Effects of workload, work environment, and job tenure on employee performance at BPS Magelang Regency - Tiara Puspa Laksitasadewi; Nany Noor Kurniyati (ARKA INSTITUTE, 2026)
The purpose of this research is analyze the effects of workload, work environment, and job tenure on employee performance at the Central Statistics Agency (BPS) of Magelang Regency. This study used an explanatory research design and a quantitative methodology. A saturation sample strategy was used to choose all 55 employees as respondents from the population. Questionnaires, field observations, and records from relevant institutions were used to gather data. The study was motivated by the limited empirical research examining workload, work environment, and job tenure simultaneously within government statistical institutions characterized by high work intensity and strict data accuracy demands. Using SPSS version 26, we ran several linear regression analyses on the collected data. The findings indicate that workload, work environment, and job tenure positively and significantly affect employee performance, both partially and simultaneously. These findings suggest that effective workload management, supportive working conditions, and employee experience play important roles in improving employee performance in public-sector organizations.